THE ROLE OF KNOWLEDGE MANAGEMENT, INNOVATION, MOTIVATION AND JOB SATISFACTION IN IMPROVING EMPLOYEE PERFORMANCE (CASE: INDONESIA) - Harmiko, Guntur Dian; Tanuwijaya, Justine; Gunawan, Andreas Wahyu (International Journal of Social Service and Research, 2024)
The purpose of this study is to examine how knowledge management affects employee creativity, motivation, and work satisfaction in Indonesia's printing sector. In 2024, questionnaires were randomly delivered to PT Penerbit Erlangga Group Jakarta employees in order to gather cross-sectional data. In order to investigate a particular population or sample, data were gathered using a quantitative approach based on positivism. Research tools were used to collect data, which were then statistically evaluated to test hypotheses. The findings indicate that while knowledge management has no detrimental effects on employee performance, it does have a favorable impact on employees' motivation, creativity, and job satisfaction in Indonesia's printing industry. Furthermore, employee performance is not positively impacted by innovation, but it is positively impacted by job satisfaction and motivation. The managerial ramifications of these results underscore how critical it is for printing companies to concentrate on initiatives that raise employee engagement and satisfaction, foster innovation, and enhance staff knowledge and abilities.